Covid-19 and Well-Being of Tertiary Students in One State University: Basis for Social Counseling Program - Aquino, John Michael D.; Reyes, Mary Grace (International Journal of Social Learning (IJSL), 2024)
Researchers explores the manifestation of students in covid-19 impact to their well-being and its significant relationship. The results served as the foundation for the Social Counseling Program. This study utilized descriptive research design and used validated survey type questionnaire. The non-random sample approach of respondents which was composed of 882 students of one State University having various campuses. The results showed that the covid-19 impact in terms of health risk, health protocols, and online learning management is strongly manifested in the lives of the students. Meanwhile, the well-being in terms of positive emotions, engagement, relationship, meaning and achievement (PERMA) is also manifested. Consequently, the study found a substantial association between the covid-19 influence and the Seligman Theory of well-being. Meanwhile, health procedures have a strong association with tertiary students' well-being, albeit with a limited degree of correlation. With this, it is recommended to evaluate the university's guidance and counseling services and interventions for students in the new normal contexts. Create appropriate interventions that will address learners' difficulties and worries about academic obstacles and overall life demands, particularly at a time of pandemic.